5-hydroxytryptamine release in the anterior hypothalamic and the hippocampal areas of cholestatic rats - YANANLI, HASAN RACİ (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Cholestasis contributes to the genesis of fatigue through several mechanisms. Among these mechanisms, affected serotonergic neurotransmission is important in the pathogenesis of central fatigue. Previously, elevated levels of 5-hydroxyindole acetic acid (5-HIAA), the metabolite of 5-hydroxytryptamine (5-HT) and increased 5-HT(2) receptor density were demonstrated in the anterior hypothalamus and in the hippocampus of bile duct resected rats (BDR), respectively. The aim of this paper is to demonstrate evoked 5-HT release in selected brain regions like anterior hypothalamus and hippocampal CA1 regions of cholestatic rats using BDR rats as an experimental model for cholestasis. In this study, we analyzed the K(+) evoked 5-HT and its metabolite 5-HIAA levels by using HPLC with electrochemical detection in the microdialysis samples collected from anterior hypothalamic and hippocampal CA1 regions of sham-operated and BDR rats (n = 6). The ratios of [5-HIAA] to [5-HT] following perfusion with 100 mM K(+) artificial cerebrospinal fluid was used for the comparison of the evoked release of 5-HT. Locomotor activity was used to assess the signs of cholestasis associated fatigue in the BDR rats. The vertical and horizontal activity counts within 15 min were found to be decreased in the BDR rats compared to sham-operated rats (p < 0.05). Besides, the number of fecal boli (an index of emotionality) was also significantly fewer in the cholestatic rats (p < 0.05). No significant difference between the sham-operated and the BDR rats was detected in the basal 5-HT and 5-HIAA levels of anterior hypothalamus. K+ stimulation yielded a more profound increase in the [5-HIAA/[5-HT] in the BDR rats (p < 0.05). The basal levels of 5-HT in CAI region of the BDR rats was found to be lower than that of sham-operated group (p < 0.05), but no significant difference was observed in terms of evoked 5-HT release in both sham-operated and BDR rats. These findings imply the presence of affected serotonergic system in cholestasis. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: bile duct resected rats; cholestasis; 5-HT; anterior hypothalamus; hippocampus; PITUITARY-ADRENAL AXIS; BETA-ENDORPHIN; LIVER-DISEASE; SEROTONIN; FATIGUE; EXERCISE; MODEL; RESPONSIVENESS; NEUROENDOCRINE; MICRODIALYSIS